2012
DOI: 10.1177/1350650112463534
|View full text |Cite
|
Sign up to set email alerts
|

The influence of piston ring geometry and topography on friction

Abstract: This article provides solution for isothermal mixed hydrodynamic conjunction of the compression ring to cylinder liner. This is obtained using the average flow model representation of Reynolds equation based on pressure- and shear-induced flow factors. In particular, the effects of compression ring axial profile along its face-width and surface topography of contiguous solids are investigated. It is shown that ring geometry may be optimized to improve lubrication, whilst care should be taken in order to avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 35 publications
4
58
0
Order By: Relevance
“…Furthermore, the inlet wedge effect varies with the state of wear of the ring edge profiles. The effect of inlet wedge height is discussed in detail in Morris et al [22]. Briefly, a larger inlet wedge causes a higher pressure gradient and can lead to greater pressure-induced shear.…”
Section: Compression Ring Face-width Geometry and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the inlet wedge effect varies with the state of wear of the ring edge profiles. The effect of inlet wedge height is discussed in detail in Morris et al [22]. Briefly, a larger inlet wedge causes a higher pressure gradient and can lead to greater pressure-induced shear.…”
Section: Compression Ring Face-width Geometry and Compositionmentioning
confidence: 99%
“…Wear of ring coatings yields transient boundary friction throughout the useful life of the ring which is also affected by changes in the ring face-width geometry [11,22]. Therefore, the surface characteristics and overall geometry of new and worn top compression rings are studied ( Figure 1).…”
Section: Compression Ring Face-width Geometry and Compositionmentioning
confidence: 99%
“…More comprehensive solutions, including 2-dimesional analysis with thermal effects, sideleakage flow and surface roughness are provided elsewhere [3,11,28,29].…”
Section: Piston Compression Ring Conjunctionmentioning
confidence: 99%
“…Their results showed that using this method can significantly reduce friction power loss. Morris et al [27] and Wu et al [28] carried out a simulation study on the influence of piston ring geometry and topography on piston ring and cylinder liner friction. Singh et al [29] used an experimental study to investigate the effect of modified profiles of the piston ring face on the performance of a diesel engine.…”
Section: Design Parameter Optimizationmentioning
confidence: 99%